2022
DOI: 10.1002/anie.202204719
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Bioisosteres: Divergent Synthesis of Azabicyclohexanes and Cyclobutenyl Amines from Bicyclobutanes**

Abstract: The development of two divergent and complementary Lewis acid catalyzed additions of bicyclobutanes to imines is described. Microscale high‐throughput experimentation was integral to the discovery and optimization of both reactions. N‐arylimines undergo formal (3+2) cycloaddition with bicyclobutanes to yield azabicyclo[2.1.1]hexanes in a single step; in contrast, N‐alkylimines undergo an addition/elimination sequence to generate cyclobutenyl methanamine products with high diastereoselectivity. These new produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
88
0
14

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 49 publications
1
88
0
14
Order By: Relevance
“…To move beyond strictly carbocyclic isosteres (whose benets of higher C sp 3 may be countered by their high clog P), Leitch and co-workers explored if BCBs could be progenitors to 2-azabicyclo[2.1.1]hexanes (aza-BCHs) through a reaction with imines (Scheme 13). 116 This hypothesis expands on the reports in the early 1980s by Amey and Dougherty, 102,103 as well as the more recent work of Lu, 27 who found that BCBs undergo strainrelieving cycloadditions upon irradiation with 1,2,4-triazoline-3,5-diones. The latter have been recently been popularized by Sarlah for dearomative cycloaddition reactions and utilized for the aforementioned bioconjugation reported by Malins.…”
Section: Bcbs As Entry Points To New Bioisosteric Spacesupporting
confidence: 75%
“…To move beyond strictly carbocyclic isosteres (whose benets of higher C sp 3 may be countered by their high clog P), Leitch and co-workers explored if BCBs could be progenitors to 2-azabicyclo[2.1.1]hexanes (aza-BCHs) through a reaction with imines (Scheme 13). 116 This hypothesis expands on the reports in the early 1980s by Amey and Dougherty, 102,103 as well as the more recent work of Lu, 27 who found that BCBs undergo strainrelieving cycloadditions upon irradiation with 1,2,4-triazoline-3,5-diones. The latter have been recently been popularized by Sarlah for dearomative cycloaddition reactions and utilized for the aforementioned bioconjugation reported by Malins.…”
Section: Bcbs As Entry Points To New Bioisosteric Spacesupporting
confidence: 75%
“…Leitch and co-workers went beyond the use of alkenes and reported the insertion of imines into BCBs in a Lewis acidcatalysed stepwise cyclisation to aza-BCHs (Fig. 5B) 88 . BCBs bearing both a carbonyl and aryl group were necessary for the reaction, but a range of typical aromatic and heteroaromatic systems were tolerated (as in 99 and 100) as were amide substituents (as in 101).…”
Section: Bridged Bicyclic Compounds By Insertionmentioning
confidence: 99%
“…However, in stark contrast to the numerous sp 3 -rich bioisosteres for ortho-and para-substituted arenes 2,9,10,12 , a geometrically-accurate bioisostere for meta-arenes is yet to be discovered. Recent reports on the use of (hetero)bicyclo[2.1.1]hexanes [13][14][15][16][17] and bridge-substituted BCPs [18][19][20] have contributed to this arena (Fig. 1b).…”
mentioning
confidence: 99%